Comparative fish ecology in three periodically connected rivers in the upper Zambezi and Okavango ecoregions - Taylor, Geraldine Claire (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2017)
The Upper Zambezi, Kavango and Kwando rivers are three periodically interlinked floodplain rivers which share the same Upper Zambezian floodplain ichthyofauna. The aim of this thesis was to compare the biology and ecology of the fish communities in these three rivers. The objective was to test the hypothesis that fish community composition and assemblage structure, fish diets, food web structure and trophic dynamics, fish growth rates and total mortality are influenced by the differing flood magnitudes of the three rivers, in support of the flood pulse concept. To understand the abiotic characteristics of each river, water temperature, flood regime, total dissolved inorganic nitrogen concentrations and water quality parameters were measured and compared between rivers. Water temperatures varied seasonally, and seven day moving averages peaked above 30 Â°C in January, and fell to between 16 and 19 Â°C in June. The Zambezi River had the largest flood (6.14 m), followed by the Kavango River (3.80 m), while the Kwando River had the smallest flood (0.65 m). Total dissolved inorganic nitrogen concentrations were low in the Kavango and Zambezi Rivers (0.2 - 0.6 mg/l), and slightly higher in the Kwando River (<1 mg/l). Conductivity, total dissolved solids and total dissolved inorganic nitrogen concentrations decreased with the flood (dilution effect). Using biomass catch per unit effort data from experimental gillnets, fish community composition and assemblage structure was described, and differed between rivers in all hydrological seasons. In the Zambezi and Kavango rivers, fish assemblages varied with hydrological season as a result of the homogenising influence of the flood pulse, while in the Kwando River fish assemblages did not differ seasonally as flood pulses were small and often irregular. Differences in community composition were attributed to the abundance of Hydrocynus vittatus, a large bodied open water predator, in the Zambezi and Kavango rivers, and its relative absence in the Kwando River. Based on the results of the community composition, six focus species were chosen that were abundant and representative of the various feeding modes and life history strategies of the fish community. These were the striped robber Brycinus lateralis, sharptooth catfish Clarias gariepinus, blunttooth catfish Clarias ngamensis, African pike Hepsetus cuvieri, silver catfish Schilbe intermedius and purpleface largemouth Serranochromis macrocephalus. Stomach contents analysis was then used to compare the feeding ecology of the six example species between rivers. Clarias gariepinus, C. ngamensis and S. intermedius were piscivorous in the Zambezi and Kavango rivers, and preyed upon more invertebrates in the Kwando River, while Hepsetus cuvieri and S. macrocephalus were piscivorous in all three rivers. Differences in diets were attributed to seasonal prey abundance, with prey fishes abundant during falling and low water when the Zambezi and Kavango rivers were sampled, while invertebrates were abundant during rising and high water when the Kwando River was sampled. Prey mastication by B. lateralis made prey identification difficult. For other predators, the usefulness of stomach contents analysis for dietary descriptions was restricted by the high proportion of empty stomachs. As a result, whole ecosystem stable isotope analysis was used to gain a holistic understanding of the food web structure and fish feeding ecology of the three rivers. The Zambezi and Kavango river food webs were supported by C enriched resources such as C4 and C3 riparian vegetation from the floodplain, while the Kwando River food web was based on C depleted resources such as filamentous algae and aquatic macrophytes. The Zambezi River food web had a restricted nitrogen range, with reduced food chain length and the predators in this river did not occupy such elevated trophic positions compared to in the Kavango and Kwando river food webs. This was attributed to the overfishing of the primary and tertiary consumers in the Zambezi River, a phenomenon known to reduce food chain length. Focussing on predator communities, in the Zambezi and Kavango rivers, H. vittatus isotopic niche width was large and overlapped significantly with most other predators, while in the Kwando River predator niches were more distinct. This supported previously proposed hypotheses by describing H. vittatus as a dominant predator which excludes all other fishes by predation or competition. Despite the dominance of H. vittatus, C. gariepinus occupied the position of top predator in all three rivers, and information on the habitat use, feeding habits and trophic niches of the serranochromine cichlids added understanding of their ecology. Lastly, age was determined using sectioned sagittal otoliths for C. gariepinus, C. ngamensis, S. intermedius and S. macrocephalus and using whole asteriscus otoliths for B. lateralis and H. cuvieri, and growth was modelled using the von Bertalanffy growth equation. Growth performance was high in the Zambezi and Kavango rivers, and lower in the Kwando River, most likely in response to the varying flood magnitudes. Total mortality rates, estimated using Hoenig's maximum-age based equation, were high in the Zambezi River as a result of the high fishing pressure on this river. Overall floodplain fish ecology in the Zambezi, Kavango and Kwando rivers was influenced by the flood pulse, as was predicted by the flood pulse concept. Periodic and equilibrium life history strategists were found to adapt either to the pulsing environments of the Zambezi and Kavango rivers, or to the more stable environment of the Kwando River, and large bodied, long lived periodic strategists such as C. gariepinus tended to be highly plastic and able to thrive in most conditions. Data also suggested that Zambezi River food web structure and fish mortality rates have been impacted by overfishing, for which more information is needed to conserve and manage this system.
Keywords: Fishes -- Ecology -- Zambia -- Zambezi District; Floodplain ecology -- Zambia -- Zambezi District; Stable isotopes; Fishes -- Food -- Zambia -- Zambezi District; Fishes -- Mortality -- Zambia -- Zambezi District; Fish populations -- Zambia -- Zambezi District; Fishes -- Growth